1996
DOI: 10.1073/pnas.93.15.7894
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive receptor activation by Crouzon syndrome mutations in fibroblast growth factor receptor (FGFR)2 and FGFR2/Neu chimeras.

Abstract: Crouzon syndrome is an autosomal dominant condition primarily characterized by craniosynostosis. This syndrome has been associated with a variety of amino acid point mutations in the extracellular domain of fibroblast growth factor receptor 2 (FGFR2). FGFR2/Neu chimeras were generated by substituting the extracellular domain of Neu with that of FGFR2 containing the following Crouzon mutations: Tyr-340->His; Cys-342->Tyr; Cys-342-*Arg; Cys- The human fibroblast growth factor receptor (FGFR) family is composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
1
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(75 citation statements)
references
References 37 publications
1
71
1
2
Order By: Relevance
“…The gain-of-function associated with the mutated FGF-Rs has been attributed to ligand-independent dimerization/activation, and more recently to increased affinity of the mutated FGF-Rs for ligand, specifically FGF-2. [2][3][4][5][6] The mechanism for ligand-independent FGF-R dimerization and subsequent activation has been attributed to disruption of intramolecular disulfide bonds in the third immu- noglobulin loop of the FGF-R as a result of a point mutation and loss of an IgIII-associated cysteine residue. [2][3][4][5] Similarly, Robertson and colleagues 36 demonstrated that FGF-R mutations not involving cysteine substitutions may disrupt intramolecular disulfide bonds by altering the conformation of the IgIII domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gain-of-function associated with the mutated FGF-Rs has been attributed to ligand-independent dimerization/activation, and more recently to increased affinity of the mutated FGF-Rs for ligand, specifically FGF-2. [2][3][4][5][6] The mechanism for ligand-independent FGF-R dimerization and subsequent activation has been attributed to disruption of intramolecular disulfide bonds in the third immu- noglobulin loop of the FGF-R as a result of a point mutation and loss of an IgIII-associated cysteine residue. [2][3][4][5] Similarly, Robertson and colleagues 36 demonstrated that FGF-R mutations not involving cysteine substitutions may disrupt intramolecular disulfide bonds by altering the conformation of the IgIII domain.…”
Section: Discussionmentioning
confidence: 99%
“…1 In vitro studies of these mutated FGF-Rs have identified at least two biomolecular mechanisms that mediate excess signaling by these receptors: 1) formation of receptor dimers in the absence of receptor ligand [ie, basic fibroblast growth factor (FGF), resulting in ligand-independent intracellular signaling; and 2) increased affinity of mutated receptors for ligand. [2][3][4][5][6] Increased FGF-biological activity is thought to lead to the premature fusion of cranial sutures and the dysmorphic craniofacial phenotype associated with these syndromes. To date, however, direct evidence supporting this hypothesis has been lacking.…”
mentioning
confidence: 99%
“…In nonosteoblastic cells, the expression of FGFR2 harboring a Crouzon mutation results in increased cell proliferation (Galvin et al 1996). In murine calvarial cells, transfection of the Fgfr2 S252W (Apert mutation) gene inhibits cell differentiation and increases proliferation (Mansukhani et al 2000).…”
Section: Control Of Cranial Suture Closure By Fgf Signalingmentioning
confidence: 99%
“…Several of the mutations in Fgfr1 and Fgfr2 in CS, PS, and JWS constitutively activate the receptor by stabilizing intermolecular disulfide bonds, causing ligand-independent dimerization and signaling (Neilson and Friesel 1995;Wilkie et al 1995a;Galvin et al 1996;Robertson et al 1998). Other mutations are thought to prolong the duration of receptor signaling or alter ligand-binding specificity (Anderson et al 1998;Mansukhani et al 2000;Plotnikov et al 2000;Yu et al 2000;Ibrahimi et al 2001).…”
Section: Fgf Receptor Mutations Induce Craniosynostosis Syndromesmentioning
confidence: 99%
“…Most Crouzon syndrome mutations involve the gain or loss of a cysteine residue within Ig domain III of FGFR2. The consequence of this class of mutation on the function of FGFR activity is to create an unpairedcysteine residue, which facilitates the formation of intermolecular disulphide bonds, causing ligand-independent dimerization, phosphorylation, and signaling (34). The mechanism of this mutation suggests that uniformly elevated FGFR signaling in one cell type is not sufficient to induce ectopic differentiation or that the intensity of receptor activation for this type of mutation is not sufficient to affect skeletal limb development.…”
mentioning
confidence: 99%